2016
DOI: 10.1155/2016/1420673
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Risk Factors Associated with Obesity between Zanzibar and Tanzania Mainland among Women of Reproductive Age Based on the 2010 TDHS

Abstract: The occurrence of overweight and obesity has serious health implications. The 2010 Tanzania Demographic and Health Survey data set was reanalysed to compare the prevalences of overweight and obesity between Mainland Tanzania and Zanzibar and to determine how demographic factors can predict overweight and obesity across the United Republic of Tanzania. About 7.92% of the Tanzanian women of reproductive age were obese, 15% were overweight, and 11.5% were underweight. Women from Mainland Tanzania (6.56%) were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Our study has shown that, there is a positive association between higher wealth-index of the households and DBMHL, especially in Bangladesh and Pakistan. Some other studies have also supported our result by revealing that, child malnutrition and maternal overweight were highly observed among middle income families [60,61]. The positive association between higher wealth-index and DBMHL are in line with one of the previous studies conducted in Bangladesh and its neighboring countries [15], but appears to be contradicted with the studies from Latin American countries, where the prevalence of DBMHL is more common in lower wealth-index groups.…”
Section: Discussionsupporting
confidence: 86%
“…Our study has shown that, there is a positive association between higher wealth-index of the households and DBMHL, especially in Bangladesh and Pakistan. Some other studies have also supported our result by revealing that, child malnutrition and maternal overweight were highly observed among middle income families [60,61]. The positive association between higher wealth-index and DBMHL are in line with one of the previous studies conducted in Bangladesh and its neighboring countries [15], but appears to be contradicted with the studies from Latin American countries, where the prevalence of DBMHL is more common in lower wealth-index groups.…”
Section: Discussionsupporting
confidence: 86%
“…For this study, women who were pregnant, or who had given birth in the two months preceding the survey were excluded to minimize measurement bias due to initial weight gain from pregnancy and childbirth, consistent with the TDHS report [24] and previously published studies [18,25,26,32]. A total of sample 11,735 reproductive age women were included in the study.…”
Section: Data Sourcementioning
confidence: 99%
“…Independent variables were selected based on previous studies from LMICs [18,19,25,26,[32][33][34][35][36][37] and data availability in the TDHS. These factors were broadly classified as socio-economic, demographic, behavioural and community-level factors.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salienta-se que, neste estudo, assim como em outros com similar delineamento, a idade manteve-se associada aos desfechos, mesmo ajustada para diversos fatores de confusão 14,[22][23][24] . A associação entre idade e sobrepeso ou obesidade pode ser parcialmente explicada pelo declínio da taxa metabólica basal e diminuição da massa muscular, que fisiologicamente acompanha o processo de envelhecimento, bem como pela redução natural da prática atividade física 3,[25][26][27] .…”
Section: ▄ Discussãounclassified